2020
DOI: 10.21037/apm-20-1720
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 with pleural effusion as the initial symptom: a case study analysis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a newly identified strain of coronavirus in the human body and was reported in Wuhan at the end of 2019. So far, the epidemic is continuing and very serious, with the number of infections and deaths increasing. Despite active investigations around the world to better understand the dynamics of transmission and the scope of clinical disease, COVID-19 continues to spread rapidly from person to person. The common signs and symptoms of SARS-CoV-2 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Some studies show that the frequency of pleural effusions varies depending on age [11,13]. In their study involving 552 patients, Majidi et al showed that pleural effusion developed more often in patients aged 50 years and older [13]. In their study, Wei et al also Bolesnica je u toku hospitalizacije lečena po protokulu za lečenje pacijenata sa KOVID-19 oboljenjem, uz postepeno poboljšanje, povlačenje simptoma bolesti i oslobađanje od kiseoničke potpore.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies show that the frequency of pleural effusions varies depending on age [11,13]. In their study involving 552 patients, Majidi et al showed that pleural effusion developed more often in patients aged 50 years and older [13]. In their study, Wei et al also Bolesnica je u toku hospitalizacije lečena po protokulu za lečenje pacijenata sa KOVID-19 oboljenjem, uz postepeno poboljšanje, povlačenje simptoma bolesti i oslobađanje od kiseoničke potpore.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, as well, a repeat X-ray, four days later, showed that the pleural effusion had disappeared (Figure 3). Some studies show that the frequency of pleural effusions varies depending on age [11,13]. In their study involving 552 patients, Majidi et al showed that pleural effusion developed more often in patients aged 50 years and older [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Et al [11] perturbation technique experienced over a moving with the influence of chemical reactionon semiinfinite vertical plateat the time of mixed convection. R. Muthucumaraswamy [12] his problem discussedwith uniform suction onregularly moving influence of a homogeneous first order chemical reaction in the vertical surface.Swetaprovo Chaudhuri et al [13] established pandemic droplet evaporation and the breathing droplet direction using a determined physical norm mathematically.Jing Zhang et al [14] analysed infected case report, who experience traumatic suffering from a vehicle accident and also persistCOVID-19,in the initial symptom with pleural effusion obtained. In the present study wedeal with new vision, how pleural fluid is contaminated due to novel corona virus occurrence of human respiratory tract with existing pulmonary disorders.…”
Section: Introductionmentioning
confidence: 99%